2017
DOI: 10.1371/journal.pone.0170215
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of Quantifying Longitudinal Brain Changes in Herpes Simplex Virus (HSV) Encephalitis Using Magnetic Resonance Imaging (MRI) and Stereology

Abstract: ObjectivesTo assess whether it is feasible to quantify acute change in temporal lobe volume and total oedema volumes in herpes simplex virus (HSV) encephalitis as a preliminary to a trial of corticosteroid therapy.MethodsThe study analysed serially acquired magnetic resonance images (MRI), of patients with acute HSV encephalitis who had neuroimaging repeated within four weeks of the first scan. We performed volumetric measurements of the left and right temporal lobes and of cerebral oedema visible on T2 weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…For the main analyses, patients in each cohort were categorised into three diagnostic groups: (i) HSV encephalitis (referred to as 'HSV'), (ii) Encephalitis of Other Identified Causes (referred to as 'Other'), and (iii) Encephalitis of Unknown Cause (referred to as 'Unknown'). This was done according to predetermined case definitions for HSV and other infectious causes [25][26][27] and autoimmune encephalitis [28]. Medical notes and discharge letters were additionally reviewed by the study's panel of infectious disease and neurology specialists.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the main analyses, patients in each cohort were categorised into three diagnostic groups: (i) HSV encephalitis (referred to as 'HSV'), (ii) Encephalitis of Other Identified Causes (referred to as 'Other'), and (iii) Encephalitis of Unknown Cause (referred to as 'Unknown'). This was done according to predetermined case definitions for HSV and other infectious causes [25][26][27] and autoimmune encephalitis [28]. Medical notes and discharge letters were additionally reviewed by the study's panel of infectious disease and neurology specialists.…”
Section: Methodsmentioning
confidence: 99%
“…Long-term outcome cohort. Patients in the long-term outcome cohort were identified by consultants across ENCEPH UK hospital sites, from the Public Health England study database [2] or they self-referred in response to a notice by the Encephalitis Society [27]. There were 81 https://doi.org/10.1371/journal.pone.0230436.g001…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, because corticosteroids cause immunosuppression, which in theory facilitates increased viral replication, their role is uncertain. 32 In other brain infections, including bacterial meningitis and tuberculous meningitis the benefit of corticosteroids has been demonstrated in large clinical trials. 33 For HSV encephalitis the potential benefit of using corticosteroid as an adjunct to aciclovir therapy has been suggested from small case series and retrospective comparisons, but there has been no prospective randomised study reported.…”
Section: Open Accessmentioning
confidence: 99%
“… 23 However, because corticosteroids cause immunosuppression, which in theory facilitates increased viral replication, their role is uncertain. 32 …”
Section: Introductionmentioning
confidence: 99%